Analysis of geotourism system in Firoozkouh township and presentation of its development model from the perspective of geopark capability - somayeh jahantigh mand; amir karam; ezat ghanavati (تحقیقات کاربردی علوم جغرافیایی, 2025)
Geotourism is one of the important types of ecotourism with a responsible and conservation-oriented approach that emphasizes the popularization of earth sciences and the cultural, social, and economic development of the local community. In order to evaluate and explain the geotourism conditions of a region and the capabilities of a destination to become a geopark, it is necessary to present and explain the optimal and desirable model for the development of geotourism destinations. Firouzkouh County, with its numerous earth heritage assets, is considered one of the areas susceptible to geotourism. Given the high potential of geotourism for development as a geopark and the lack of necessary utilization of these capabilities in the development of the county, it is necessary to present an optimal model for analyzing the development of geopark capabilities in the county. In this research, through library and survey methods and using geotourism evaluation methods including the Facilas method, the GAM method, and the terrestrial diversity sites method, the county's geosites were evaluated and analyzed from the perspective of different values. The results show that most of the geosites in the region, despite their high representation, educational potential, and aesthetic value, have a weak connection with the local community, and their vulnerability and risk of extinction are increasing. Also, from the perspective of assessing the geopark capabilities, it was determined that this county currently does not have the capability to become an independent geopark. Accordingly, a model for developing the county's capability to become a geopark has been presented, which mainly emphasizes participatory management, entrepreneurship, multipurpose tourists, and geotourism typology, etc.